A PxL motif promotes timely cell cycle substrate dephosphorylation by the Cdc14 phosphatase - Kataria, Meghna; Mouilleron, Stephane; Seo, Moon-Hyeong; Corbi-Verge, Caries; Kim, Philip M.; Uhlmann, Frank (NATURE PUBLISHING GROUP, 2018)
The cell division cycle consists of a series of temporally ordered events. Cell cycle kinases and phosphatases provide key regulatory input, but how the correct substrate phosphorylation and dephosphorylation timing is achieved is incompletely understood. Here we identify a PxL substrate recognition motif that instructs dephosphorylation by the budding yeast Cdc14 phosphatase during mitotic exit. The PxL motif was prevalent in Cdc14-binding peptides enriched in a phage display screen of native disordered protein regions. PxL motif removal from the Cdc14 substrate Cbk1 delays its dephosphorylation, whereas addition of the motif advances dephosphorylation of otherwise late Cdc14 substrates. Crystal structures of Cdc14 bound to three PxL motif substrate peptides provide a molecular explanation for PxL motif recognition on the phosphatase surface. Our results illustrate the sophistication of phosphatase-substrate interactions and identify them as an important determinant of ordered cell cycle progression.
Keywords: MITOTIC-EXIT; SACCHAROMYCES-CEREVISIAE; GLOBAL ANALYSIS; PHAGE DISPLAY; PROTEIN PHOSPHATASE; ANAPHASE ONSET; PHOSPHORYLATION; CDK; SPECIFICITY; MITOSIS